Preparation and characterization of magnetic chitosan and its application for preconcentration of platinum(IV) metal ions - Mohd Daud, Jamaluddin; Ahmad, Nurliza (2008)
Magnetic chitosan beads were prepared by 3 different weight ratios of Fe3O4 : chitosan, i.e. 1:1, 5:1 and 10:1, and were cross-linked with glutaraldehyde. Physical characterizations of the beads were carried out by scanning electron microscope (SEM), image analyzer, Fourier transformed infrared spectrometer (FTIR) and vibrating-sample magnetometer (VSM). The influence of pH, contact time and platinum (IV) ions concentration were studied in order to achieve the optimum adsorption conditions by solid phase extraction (SPE) method of static mode. Recovery of the adsorbed platinum (IV) ions from the beads was carried out by desorption with 1.0 M ammonium thiocyanate solution.